Diet Quality and Visceral Adiposity among a Multiethnic Population of Young, Middle, and Older Aged Adults. Issue 6 (26th May 2020) - Panizza, Chloe E; Wong, Michael C; Kelly, Nisa; Liu, Yong En; Shvetsov, Yurii B; Lowe, Dylan A; Weiss, Ethan J; Heymsfield, Steven B; Kennedy, Samantha; Boushey, Carol J; Maskarinec, Gertraud; Shepherd, John A
ABSTRACT: Background: Visceral adiposity, more so than overall adiposity, is associated with chronic disease and mortality. There has been, to our knowledge, little research exploring the association between diet quality and visceral adipose tissue (VAT) among a mulitethnic population aged 18–80 y. Objective: The primary objective of this cross-sectional analysis was to examine the association between diet quality [Healthy Eating Index–2010 (HEI-2010) scores] and VAT among a multiethnic population of young, middle, and older aged adults in the United States. Secondary objectives were to repeat these analyses with overall adiposity and blood-based biomarkers for type 2 diabetes and cardiovascular disease risk as outcome measures. Methods: A total of 540 adults (dropped out: n = 4; age: 18–40 y, n = 220; 40–60 y, n = 183; 60–80 y, n = 133) were recruited across 3 sites (Honolulu County, San Francisco, and Baton Rouge) for the Shape Up! Adults study. Whole-body DXA, anthropometry, fasting blood draw, and questionnaires (food frequency, physical activity, and demographic characteristics) were completed. Linear regression was used to assess the associations between HEI-2010 tertiles and VAT and secondary outcome measures among all participants and age-specific strata, while adjusting for known confounders. Results: VAT, BMI (kg/m 2 ), body fat percentage, total body fat, trunk fat, insulin, and insulin resistance were inversely related to diet quality (all P values < 0.004). When stratified by age, diet quality was inversely associated with VAT among participants aged 60–80 y ( P < 0.006) and VAT/subcutaneous adipose tissue (SAT) among participants aged 40–60 y ( P < 0.008). Conclusions: Higher-quality diet was associated with lower VAT, overall adiposity, and insulin resistance among this multiethnic population of young, middle, and older aged adults with ages ranging from 18 to 80 y. More specifically, adherence to a high-quality diet may minimize VAT accumulation in adults aged 60–80 y and preferentially promote storage of SAT compared with VAT in adults aged 40–60 y. This study was registered at clinicaltrials.gov as NCT03637855.